Analisis Pengaruh Ekspor dan Impor Terhadap Pertumbuhan Ekonomi di Indonesia Periode 2019-2023 - Mandai, Nalla Azzahra; Amelia, Marsya; Kamila, Vita Elma; Bramantya, Naurah Hasanah; Desmawan, Deris (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
In a country, economic sector growth is an increase in per capita output. When a country's economic growth increases, its capacity to meet the needs of its citizens also increases, thereby improving their overall welfare. Economic growth in Indonesia occurs from many factors, one of which is exports and imports. This study aims to analyze how the value of Indonesia's exports and imports in the 2019-2023 period affects its economic growth. This research applies secondary data in the form of time series covering the time span. The data is obtained through data statistics and previous journals. The application of the method utilized by researchers in this study is the OLS (Ordinary Least Square) method. The tests applied are partial data testing (T-test) and simultaneous data testing (F-test). The regression equation in this study is Y = 4.264 - 5.579EX1 + 9.323EX2. Exports have such an impact on Indonesia's economic growth that is fully supported by the results of the t-test. Similarly, imports also show a significant influence on economic growth at the country level. The reason why economic growth is not affected is because of the influence of other variables.